Processus de cadrage et mouvements sociaux : une analyse du débat sur la prostitution dans le mouvement féministe espagnol au prisme de l’œuvre littéraire de Virginie Despentes - Pilar Pinto Buzón (Amnis)
Based on qualitative research on the reception of Virginie Despentes within the Spanish feminist movement, this work is framed within an interdisciplinary perspective that, through an ad hoc qualitative methodology, has allowed us to tangibly explore the influence of the French author's texts on activist practices. The theory of framing processes proposed by David A. Snow and Robert D. Benford for the study of social movements and collective action is employed in this case study to examine the active role of literature in the construction of social movements. This approach has allowed us to highlight some of the dialectical conflicts currently traversing the Spanish feminist movement.